Preliminary Study of Life Cycle Assessment on Food Surplus Redistribution Compared to Food Waste Management in Surabaya - Khairunisa; Nuzulul Anggi Rizki; Lies Wuryanita Adriani; Rizki Ainuna Wijaya (Poltekkes Kemenkes Surabaya, 2026)
Food waste accounts for approximately 40% of total waste generation in Indonesia and contributes significantly to national greenhouse gas (GHG) emissions. While most food waste is still disposed of in landfills, food surplus redistribution through food banks has emerged as a potential mitigation strategy. This study evaluates the environmental performance of food surplus redistribution compared to conventional food waste management options using a life cycle assessment (LCA) approach. The analysis was conducted at Garda Pangan, Surabaya, with a functional unit of 1 ton of food surplus and assessed three scenarios: (1) landfill disposal, (2) composting and anaerobic digestion, and (3) food surplus redistribution. The assessment applied the CML IA Baseline method and focused on Global Warming Potential (GWP), using SimaPro 9.0 and the Ecoinvent 3 database. The results show that landfill disposal has the highest GWP at 1,920 kg CO₂-eq per ton of food waste, driven primarily by methane emissions from anaerobic decomposition. Composting and anaerobic digestion result in lower impacts, at 1,503 and 1,730 kg CO₂-eq per ton, respectively. In contrast, food surplus redistribution shows a markedly lower GWP of 1.24 kg CO₂-eq per ton of food surplus, as emissions are dominated by transportation activities within a simplified gate-to-gate system boundary. This preliminary analysis relied on secondary inventory data and excluded potential avoided food production impacts; therefore, the estimated GWP for redistribution may underestimate or overestimate actual emissions. These findings highlight the importance of prioritizing food waste prevention and the benefits of food surplus redistribution within integrated waste management strategies to reduce GHG emissions while delivering social co-benefits.